2019
DOI: 10.1111/jpn.13170
|View full text |Cite
|
Sign up to set email alerts
|

Proteome changes in renal cortex and medulla induced by dietary supplementation with inulin‐type fructans in growing pigs

Abstract: The aim of the study was to evaluate the influence of dietary supplementation with inulin extract from chicory root and dried chicory root on the protein profile of the renal cortex and medulla of growing pigs. The experiment was carried out on renal cortex and medulla tissue collected from 24 50‐day‐old PIC x Penarlan P76 crossbred piglets (males). Animals were divided into three dietary groups (n = 8) and fed with a control diet, diet supplemented with 2% inulin extract from chicory root and a diet supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For instance, in trials with companion animals it has been shown that dried whole chicory roots, as a source of prebiotic fibers, provided health benefits and contributed to longevity ( 149 , 150 ). Consequently, whole chicory roots are now also tested in studies with domestic animals for their potential as nutritive and health-promoting feed components ( 151 154 ).…”
Section: Contemporary Uses Of Chicory Rootsmentioning
confidence: 99%
“…For instance, in trials with companion animals it has been shown that dried whole chicory roots, as a source of prebiotic fibers, provided health benefits and contributed to longevity ( 149 , 150 ). Consequently, whole chicory roots are now also tested in studies with domestic animals for their potential as nutritive and health-promoting feed components ( 151 154 ).…”
Section: Contemporary Uses Of Chicory Rootsmentioning
confidence: 99%
“…Identification of biomarkers or tracking changes in sample chemical components may often signal the presence of physiological conditions requiring treatment regimens. Table-3 summarizes recent applications of MALDI-TOF for diagnostics based on molecular typing [138][139][140][141][142][143][144][145][146][147][148][149][150][151][152][153][154]. For the first example, Riengvirodkij et al [138] used MALDI-TOF in effort to identify peptide biomarkers associated with mitral valve disease in dogs.…”
Section: Matrix-assisted Laser Desorption Ionizationtime-of-flight Fo...mentioning
confidence: 99%
“…Feed additives for beef cattle and swine operations are continuously evaluated for affecting the operation's bottom line. Robak et al [149] have studied the effect of inulin extract and chicory root on protein expression in the renal cortex and medulla of male pigs. Matrix-assisted laser desorption ionization-time-offlight was used for protein identification.…”
Section: Matrix-assisted Laser Desorption Ionizationtime-of-flight Fo...mentioning
confidence: 99%
“…Additionally, both dietary additives increase the expression of proteins related to hepatocyte protection against oxidative stress ( 44 ). Diet supplementation with dried Chicory root or inulin causes significant changes in the expression of liver cytoskeletal proteins, and alters the expression of kidney proteins engaged in energy metabolism and stress response in pigs ( 45 ). Moreover, Chicory root supplements have a potential ability to improve the liver mineral content oxidoreductive homeostasis in growing pigs ( 46 ).…”
Section: Pharmacological Applications Of Phytochemicals In Pig Productionmentioning
confidence: 99%